2021
DOI: 10.3389/fendo.2021.610573
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Thyroid Hemorrhage Caused by Langerhans Cell Histiocytosis: A Case Report and Literature Review

Abstract: PurposeLangerhans cell histiocytosis (LCH) is a rare clonal disorder of Langerhans antigen-presenting cells. However, thyroid LCH involvement is relatively rare. We present the first case of spontaneous thyroid hemorrhage due to LCH progression and discuss the clinical features, diagnosis, and treatments of thyroid LCH in a literature review.MethodsClinical data were collected. Previously published articles on thyroid LCH involvement were reviewed to assess the clinical features, diagnosis, and treatments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…As for thyroid function status, it has been reported that 37.9-40.9% of patients have euthyroidism, 19.7%-31.03% have hypothyroidism, 6.9%-10.6% have subclinical hypothyroidism, and 1.5%-3.45% have hyperthyroidism (11,12). Our results largely parallel these reports.…”
Section: Thyroid Langerhans Cell Histiocytosis Together With Papillar...supporting
confidence: 89%
See 1 more Smart Citation
“…As for thyroid function status, it has been reported that 37.9-40.9% of patients have euthyroidism, 19.7%-31.03% have hypothyroidism, 6.9%-10.6% have subclinical hypothyroidism, and 1.5%-3.45% have hyperthyroidism (11,12). Our results largely parallel these reports.…”
Section: Thyroid Langerhans Cell Histiocytosis Together With Papillar...supporting
confidence: 89%
“…Furthermore, neck pain and obstructive symptoms like dyspnea are rare. Zhang reported a rare case of painful neck swelling and progressive dyspnea diagnosed as a spontaneous thyroid hemorrhage (12).…”
Section: Thyroid Langerhans Cell Histiocytosis Together With Papillar...mentioning
confidence: 99%
“…The patient had no smoking habit, but chest CT was still strongly recommended in the future (31). Fine needle aspiration cytology can preliminarily diagnose most thyroid diseases, but the diagnosis of LCH of the thyroid using FNAC is challenging due to the similarity in HE morphology between PTC cells and LCH cells (8,32). In Table 1, only 64.7% of PTC, 41.2% of LCH, and 29.4% of LCH concurrent with PTC were identified among the 22 cases which underwent preoperative FNAC examination.…”
Section: Discussionmentioning
confidence: 99%
“…Patten et al [ 8 ] reviewed a total of 65 cases of LCH involving the thyroid reported from 1961 to 2011 and found that 59% of LCH cases involving the thyroid presented as diffuse thyroid lesions, 25.8% as nodular enlargement, and 13.6% as heterogeneous enlargement. Zhang et al [ 9 ] analysed the clinical data of 29 LCH patients with thyroid involvement reported in the literature from January 2010 to April 2020. A total of 62.07% of the patients presented with goitre or diffuse goitre, and 37.93% presented with single or multiple thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of thyroid function, Patten et al [ 8 ] reported that 40.9% of patients had normal thyroid function, 19.7% had hypothyroidism, 10.6% had subclinical hypothyroidism, and 1.5% had hyperthyroidism. Zhang et al [ 9 ] and Cai et al [ 10 ] also suggested that thyroid function may show different manifestations in patients with LCH involving the thyroid. Our patient had a thyroid nodule with no clinical discomfort and normal thyroid function, as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%